2022
DOI: 10.1186/s12983-022-00473-w
|View full text |Cite
|
Sign up to set email alerts
|

Energy acquisition strategy for reproduction in a semelparous squid

Abstract: Background Energy demand for reproduction leads to a wide diversity of foraging and life-history strategy among wild animals, linking to a common objective to maximize reproductive success. Semelparous squid species in particular can use up to 50% of the total energy intake for reproduction. However, the energy acquisition strategy for reproduction is still a controversial issue regarding whether the squid shift in diet ontogenetically. Here we used Argentinean shortfin squid (Illex argentinus)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…Other studies have reported that energy was only weakly related to mantle length in the Argentine shortfin squid Illex argentinus (Lin et al. 2022; Song et al. 2023).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Other studies have reported that energy was only weakly related to mantle length in the Argentine shortfin squid Illex argentinus (Lin et al. 2022; Song et al. 2023).…”
Section: Discussionmentioning
confidence: 94%
“…These species showed high variability in ED at a given size, and only weak effects of size were evident for Silver Hake and longfin inshore squid. Other studies have reported that energy was only weakly related to mantle length in the Argentine shortfin squid Illex argentinus (Lin et al 2022;Song et al 2023). All three moderate-quality species have broad distributions: the Silver Hake is more temperate, the northern shortfin squid is boreal and temperate to subtropical, and the longfin inshore squid is temperate to subtropical.…”
Section: Moderate-quality Preymentioning
confidence: 86%
See 2 more Smart Citations